Mythologizing the Memory of Gloriana - GARROURI, Sihem (Anafora, 2023)
Consideration of Anne Bradstreet’s poem “In Honour of That High and Mighty Princess, Queen Elizabeth, of Most Happy Memory” (1643) draws our attention to the paramount significance of mythical imagery in shaping Elizabeth I’s posthumous reputation. The examination of this poem illustrates the ways in which Elizabeth’s memory is glorified and discusses the elegiac mythical reconstruction of her image by what Schweitzer aptly labelled a “gendered poetic voice” (307). This project shows that the poet makes good use of myth to write Elizabeth’s afterlife image. It scrutinizes Bradstreet’s mythological depiction of the last Tudor monarch, Queen Elizabeth I, illustrating how a woman poet rewrites the identity of a female sovereign. A close analysis of various mythical, elegiac images celebrating Elizabeth allows us to evaluate Bradstreet’s contribution to her myth-creation. It examines three mythical representations: Elizabeth as an incomparable leader, a Phoenix Queen, and a warrior Amazonian monarch.